Herbo-dentistry- A review - Nandita Gautam; Shivalingesh KK; Arjun Singh; Varnika Singh; Deepshikha Rajpoot (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Phytotherapy is the study of the use of extracts from the natural origin as medicines or health-promoting agents. Plant products have long been used in dentistry as part of various dental materials right from impression materials to eugenol, which forms an integral part of the dental clinic. The use of herbs in dental practice is not limited to only material sciences. A single herb shows a variety of effects like anti-inflammatory, antibacterial, antifungal activity, and many more. Hence the incorporation of these herbs in dental practice will prove to be a valuable adjunct to dental treatment.